1997
DOI: 10.1107/s0108768196009019
|View full text |Cite
|
Sign up to set email alerts
|

4f-Electron Density Distribution in Crystals of CeB6 at 165 K and its Analysis Based on the Crystal Field Theory

Abstract: Abstract4f-Electron density in single crystals of CeB 6, cerium hexaboride, was measured at 165 K by X-ray diffractometry. Significant peaks 2.0eA -3 high were found along the (100) directions at 0.41A from Ce on the deformation density map. Analysis based on the crystal field theory removed the peaks, confirming that they were due to the Ce 4f-electrons on the tlu-orbital. The deformation density in the B 6 octahedron was also markedly improved by the analysis and coincides qualitatively with a theoretical mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Furthermore, from an x-ray diffraction experiment on CeB 6 , Tanaka et al suggested that at 165 K, B 6 donates 1.5 electrons to the Ce, more consistent with a covalent picture than the ionic one. 11 Recent research from their group also shows that the crystal field in CeB 6 varies with temperature because of charge transfer from B 2p to Ce 5d. 12 In this paper, we report measurements of the L 3 -and L 1edge XANES and the corresponding 2p3d (L α1,2 ) and 2s(5p + valence p) (L γ 4 ) RIXS for CeB 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, from an x-ray diffraction experiment on CeB 6 , Tanaka et al suggested that at 165 K, B 6 donates 1.5 electrons to the Ce, more consistent with a covalent picture than the ionic one. 11 Recent research from their group also shows that the crystal field in CeB 6 varies with temperature because of charge transfer from B 2p to Ce 5d. 12 In this paper, we report measurements of the L 3 -and L 1edge XANES and the corresponding 2p3d (L α1,2 ) and 2s(5p + valence p) (L γ 4 ) RIXS for CeB 6 .…”
Section: Introductionmentioning
confidence: 99%
“…7 The electronic structure of CeB 6 has been subjected to many experimental investigations. Various spectroscopic [8][9][10] as well as diffraction techniques 11,12 have been applied. These previous experimental works, however, did not lead to the same conclusions, showing wide discrepancies.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 There are surprisingly few methods for directly measuring electron density distributions, and most techniques that purport to do so are based on empirical correlations. In some cases, electron density distributions can be measured with very high accuracy diffraction data; X-ray studies of 4f electron density in CeB 6 21 and 3d density in Ni(ND 3 ) 4 (NO 2 ) 2 22 are recent examples. Spin density distributions are also recoverable from magnetic resonance measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Cerium hexaboride is the material of choice because it is a strongly correlated electron material whose bonding electron density has previously presented significant challenges in terms of both theoretical modelling and experimental measurement by X-ray diffraction (Tanaka et al, 1997;Tanaka & Onuki, 2002;Makita et al, 2007Makita et al, , 2008. QCBED has the potential to cast new light on this material in terms of its bonding structure.…”
Section: Introductionmentioning
confidence: 99%